The Influence of Promotion and Location on Customer Loyalty at FamilyMart Danau Agung Dua with Social Media as a Moderator - Imam Suryono; Citra Widya Sihotang; Ari Soetiyani (SAFE-Network, 2026)
This study aims to examine the influence of promotion and location on customer loyalty at FamilyMart Danau Agung Dua, with social media serving as a moderating variable. Using a quantitative approach, the research involved 140 respondents and applied structural equation modelling with SmartPLS to analyze both direct and moderating effects among variables. The findings reveal that promotion, location, and social media each have a significant effect on customer loyalty. Furthermore, social media moderation strengthens the relationship between promotion and customer loyalty, as well as between location and customer loyalty, leading to the acceptance of all hypotheses. These results provide a deeper understanding of the factors influencing customer loyalty and offer practical implications for academics, researchers, and business practitioners. For academics, the study serves as a useful reference in exploring consumer behavior within the retail sector. For researchers, expanding the sample size is recommended to ensure more accurate and sustainable findings. For businesses such as FamilyMart, it is essential to pay attention to customer needs, design customer-friendly strategies, and leverage social media effectively to attract, retain, and strengthen customer loyalty.